2016
DOI: 10.1161/jaha.116.003217
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Renin‐Angiotensin System Inhibitors on Long‐Term Clinical Outcomes of Patients With Coronary Artery Spasm

Abstract: BackgroundCoronary artery spasm (CAS) is a well‐known endothelial dysfunction, and a major cause of vasospastic angina (VSA). The renin–angiotensin system (RAS) is known to be closely associated with endothelial function. However, there are only a few studies that investigated the impact of RAS inhibitor on long‐term clinical outcomes in VSA patients.Methods and ResultsA total of 3349 patients with no significant coronary artery disease, diagnosed with CAS by acetylcholine provocation test were enrolled for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…One case had 70% restenosis in stents, two cases had 30% restenosis in stents and the other stents had good adherence and no obvious restenosis. The effective rate of CCB in VA patients in Japan was 92.5% [16] which is similar to our stenting group (88%)and stent-free group(89%) Other literatures reported that aspirin, statins and ACEi could prevent spasm and improve the prognosis of patients [17][18][19] . In addition, we included VA patients,whose diagnostic criteria included resting angina and transient elevation of ST segment one ECG without spasm provocation test, but could be diagnosed as VA with high specificity [10,20,21] , it has been reported that provocation test is safe and effective for VA patients with no significant stenosis [22] ,but provocation test has more advantages than disadvantages for VA patients with severe stenosis [23] , We believe that provocation test may lead to unstable plaque shedding, which increases the incidence of MACE and affects the results of the trial.…”
Section: Discussionsupporting
confidence: 86%
“…One case had 70% restenosis in stents, two cases had 30% restenosis in stents and the other stents had good adherence and no obvious restenosis. The effective rate of CCB in VA patients in Japan was 92.5% [16] which is similar to our stenting group (88%)and stent-free group(89%) Other literatures reported that aspirin, statins and ACEi could prevent spasm and improve the prognosis of patients [17][18][19] . In addition, we included VA patients,whose diagnostic criteria included resting angina and transient elevation of ST segment one ECG without spasm provocation test, but could be diagnosed as VA with high specificity [10,20,21] , it has been reported that provocation test is safe and effective for VA patients with no significant stenosis [22] ,but provocation test has more advantages than disadvantages for VA patients with severe stenosis [23] , We believe that provocation test may lead to unstable plaque shedding, which increases the incidence of MACE and affects the results of the trial.…”
Section: Discussionsupporting
confidence: 86%
“…The design of this registry has been introduced before. [2,1114] In brief, it is a single-center, observational, prospective, all-comers registry designed to reflect the “real world” practice since 2004. Data were collected by a trained study-coordinator with a standardized case report form.…”
Section: Methodsmentioning
confidence: 99%
“…The design of the ACH provocation test has been introduced before. [2,1114] Initial investigation for CAG included clinical history taking and non-invasive stress tests such as treadmill test, stress echocardiography, and radionuclide study. CAG was performed to confirm the presence of significant CAD.…”
Section: Methodsmentioning
confidence: 99%
“…The design of this registry has been described previously in detail. 9 10 11 12 13 14 Data were collected by a trained study-coordinator with a standardized case report form. Standardized definitions of all patient-related variables and clinical diagnoses were used.…”
Section: Methodsmentioning
confidence: 99%
“…The design of the Ach provocation test has been described before. 9 10 11 12 13 Initial investigation for CAG included clinical history taking and non-invasive stress tests, such as treadmill test, stress echocardiography, and radionuclide study. Then, CAG was performed to confirm the presence of significant CAD.…”
Section: Methodsmentioning
confidence: 99%